2021
DOI: 10.1371/journal.pcbi.1008730
|View full text |Cite
|
Sign up to set email alerts
|

DEXOM: Diversity-based enumeration of optimal context-specific metabolic networks

Abstract: The correct identification of metabolic activity in tissues or cells under different conditions can be extremely elusive due to mechanisms such as post-transcriptional modification of enzymes or different rates in protein degradation, making difficult to perform predictions on the basis of gene expression alone. Context-specific metabolic network reconstruction can overcome some of these limitations by leveraging the integration of multi-omics data into genome-scale metabolic networks (GSMN). Using the experim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…There are many other MEMs available that were not systematically tested in this or other studies, including recent methods that account for trancriptomic variability (Joshi et al, 2020), use ensemble modeling to improve predictions (Rodríguez-Mier et al, 2021), or combine multiple methods and settings (Vieira et al, 2022). Notably, some methods integrate metabolic tasks into the model extraction procedure itself by requiring agreement with inferred task feasibility for human models and data (Agren et al, 2014;Richelle et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many other MEMs available that were not systematically tested in this or other studies, including recent methods that account for trancriptomic variability (Joshi et al, 2020), use ensemble modeling to improve predictions (Rodríguez-Mier et al, 2021), or combine multiple methods and settings (Vieira et al, 2022). Notably, some methods integrate metabolic tasks into the model extraction procedure itself by requiring agreement with inferred task feasibility for human models and data (Agren et al, 2014;Richelle et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Ensemble modeling could also help improve the models themselves by applying machine learning to their contents and predictions (Medlock and Papin, 2020). Indeed, recent studies have demonstrated context-specific ensemble modeling with a single MEM (Rodríguez-Mier et al, 2021) and combined multiple MEMs to build a single model (Vieira et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Ensemble modeling could also help improve the models themselves by applying machine learning to their contents and predictions [48]. Indeed, recent studies have demonstrated context-specific ensemble modeling with a single MEM [49] and combined multiple MEMs to build a single model [50].…”
Section: /27mentioning
confidence: 99%
“…The methodology allows the creation of not correlated PCs, letting the information of linearly correlated variables to be represented in one PC. These permit the construction of an estimated biologically significant variable (Rodríguez-Mier et al, 2021) and provides a way to limit the potential for overfitting (Wörheide et al, 2021).…”
Section: Dimensionality Reduction: Principal Component Analysismentioning
confidence: 99%